PEMIKIRAN KI HAJAR DEWANTARA DALAM KONTEKS MEMERDEKAKAN PESERTA DIDIK - Norma Aryani Damarayu; Sulianto, Joko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This discussion thoughts of Ki Hajar Dewantara in the context of education that liberates students. This research highlights the importance of education that not only focuses on cognitive development but also the affective, psychomotor, and conative aspects of students. In the era of globalization and technological advancements, emancipatory education remains relevant to address the challenges of the 21st century. This study identifies several student-centered learning strategies based on Ki Hajar Dewantara's thoughts, such as differentiated learning, culturally responsive teaching, and teaching at the right level. The implementation of these strategies is expected to liberate students in the learning process and prepare them with relevant skills for success in the modern era. This research concludes that emancipatory education can produce individuals who are independent, creative, critical, and possess good character, in line with the values taught by Ki Hajar Dewantara.